Corneal Irregular Astigmatism and Curvature Changes After Small Incision Lenticule Extraction: Three-Year Follow-Up. Issue 7 (July 2018) - Sideroudi, Haris; Lazaridis, Apostolos; Messerschmidt-Roth, Anke; Labiris, Georgios; Kozobolis, Vassilios; Sekundo, Walter
Abstract : Purpose: To evaluate the long-term changes in anterior and posterior corneal irregular astigmatism and curvatures after small incision lenticule extraction (SMILE). Methods: Fifty eyes of 28 patients underwent SMILE for myopic astigmatism. All procedures were performed using the VisuMax® femtosecond laser. A Scheimpflug camera was used for preoperative and 3-year postoperative tomography. Anterior and posterior corneal Fourier parameters (spherical component, regular astigmatism, asymmetry, and irregularity) and curvature data were evaluated and compared within 2 subgroups according to the magnitude of the refractive correction (low myopia group: spherical equivalent (SEQ) ≥ −6 D; high myopia group: (SEQ) < −6 D). Associations between all studied parameters were examined. Results: Three years postoperatively, an increase in anterior corneal curvatures and Fourier parameters was detected and the results were strongly correlated with the preoperative SEQ, lenticule thickness, and volume. At the posterior cornea, the flattest radius, corneal astigmatism, spherical component, regular astigmatism, and irregularity decreased only in the high myopia group. A correlation was found between changes in posterior astigmatism and changes in anterior radii (R = 0.349, P = 0.014), SEQ (R = 0.396, P = 0.0049), and lenticule thickness (R = −0.414, P = 0.0031). Moreover, changes in posterior corneal irregularity correlated with the changes in anterior and posterior radii (R = −0.3, P = 0.034, and R = 0.449, P = 0.0012, respectively), changes in preoperative SEQ (R = 0.284, P = 0.0477), and lenticule thickness (R = −0.311, P = 0.0298). Conclusions: Three years after SMILE, there was a reduction of posterior astigmatism in high refractive corrections. This could result in undercorrection in high refractive treatments. Total irregularities increased despite the compensatory effect of the posterior corneal surface.